2010
DOI: 10.1111/j.1365-2311.2010.01249.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental strategies in an invasive spider: constraints and plasticity

Abstract: 1. Growth defines the major life‐history traits such as size, weight, and age at maturity that determine an organism's fitness. Different models have been developed to describe growth by means of geometric progressions (e.g. Dyar's rule). However, growth forced along a geometric trajectory might constrain a plastic response to variable environmental conditions (e.g. food availability). 2. The present study investigated growth patterns under varying food conditions in the bridge spider, Larinioides sclopetarius… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…Growth patterns and rules in spiders, the largest group of invertebrate predators, are poorly studied, but in general they follow a geometric progression, known as Dyar's rule (Kleinteich & Schneider 2011;Suter & Stratton 2011). The smooth log-log regression curves actually cloak the discontinuous nature of spider growth mandated by molting of the cuticle from one instar to another.…”
Section: Nest Hole Size Preference In Immature Spidersmentioning
confidence: 99%
“…Growth patterns and rules in spiders, the largest group of invertebrate predators, are poorly studied, but in general they follow a geometric progression, known as Dyar's rule (Kleinteich & Schneider 2011;Suter & Stratton 2011). The smooth log-log regression curves actually cloak the discontinuous nature of spider growth mandated by molting of the cuticle from one instar to another.…”
Section: Nest Hole Size Preference In Immature Spidersmentioning
confidence: 99%
“…A reduction in body size following food limitation has been reported in several arthropods (Bauerfeind and Fischer , Boggs and Freeman , Dmitriew and Rowe ). Yet in bridge spiders, previous studies have shown that food limited females will delay maturation but mature at a similar size as individuals provided with abundant food (Kleinteich and Schneider , ). Hence, this provides an interesting study system in which to compare the effects of juvenile and adult food limitation on lifetime reproductive success because it is unlike some other arthropod species in which a reduction in adult body size is a common mechanism through which juvenile food limitation affects female fecundity (Bauerfeind and Fischer , Boggs and Freeman , Dmitriew and Rowe ).…”
mentioning
confidence: 95%
“…In addition to analysis of variance, we used Hedges’ g effect size to quantify the relative effects of juvenile and adult food limitation on fecundity and longevity. We predicted that juvenile food availability would have limited effects on lifetime reproductive success and lifespan compared to adult food availability, especially since juvenile food limitation does not affect adult body size (Kleinteich and Schneider , ).…”
mentioning
confidence: 99%
“…Growth patterns and rules in spiders, the largest group of invertebrate predators, are poorly studied, but in general they follow a geometric progression, known as Dyar's rule (Kleinteich & Schneider 2011;Suter & Stratton 2011). The smooth log-log regression curves actually cloak the discontinuous nature of spider growth mandated by molting of the cuticle from one instar to another.…”
Section: Nest Hole Size Preference In Immature Spidersmentioning
confidence: 99%